2006
DOI: 10.1080/09670260500480926
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity ofAphanizomenon ovalisporum(Cyanobacteria) in a Spanish water reservoir

Abstract: The summer phytoplankton population in the Arcos reservoir (Spain), an oligotrophic/mesotrophic waterbody, was dominated by the cyanobacterium Aphanizomenon ovalisporum, accompanied by Planktothrix cf. agardhii and smaller proportions of other cyanobacterial species. The bloom remained for approximately 1 month in the summer of 2004. The Arcos reservoir had moderate conductivity, up to 1756 mS cm À1, and relatively high nutrient concentrations. Planktonic biomass collected during the bloom period was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 29 publications
3
63
2
1
Order By: Relevance
“…A. ovalisporum is a major source of CYN not only in subtropical and tropical areas of Australia, the United States (Florida), and Israel (9) but also in Mediterranean Europe, where A. ovalisporum can be considered the main CYN producer to date (56)(57)(58). Studies have shown levels of 9.4 to 18 g CYN liter Ϫ1 during A. ovalisporum blooms in Spain and Italy (57,58). A. ovalisporum is characterized by its genetic homogeneity worldwide (9; this study) and an unusually high proportion of CYN-producing strains, although 2 non-CYN-producing strains have recently been reported from Lake Kinneret, Israel (29).…”
Section: Discussionmentioning
confidence: 99%
“…A. ovalisporum is a major source of CYN not only in subtropical and tropical areas of Australia, the United States (Florida), and Israel (9) but also in Mediterranean Europe, where A. ovalisporum can be considered the main CYN producer to date (56)(57)(58). Studies have shown levels of 9.4 to 18 g CYN liter Ϫ1 during A. ovalisporum blooms in Spain and Italy (57,58). A. ovalisporum is characterized by its genetic homogeneity worldwide (9; this study) and an unusually high proportion of CYN-producing strains, although 2 non-CYN-producing strains have recently been reported from Lake Kinneret, Israel (29).…”
Section: Discussionmentioning
confidence: 99%
“…Cylindrospermopsin (CYN) is one of the common members of cyanotoxins which always cause human injury. CYN originates from several cyanobacteria, such as Cylindrospermopsis raciborskii [3], Umezakia natans [4], Aphanizomenon ovalisporum [5], Anabaena bergii [6], Raphidiopsis curvata [7], Aphanizomenon flos-aquae [8], Anabaena lapponica [9], Lyngbya wollei [10] and Aphanizomenon gracile [11]. CYN has neurotoxic effects (inhibition of protein synthesis by binding to liver DNA and forms single DNA adducts which results in liver damage), hepatotoxic effects (inhibition of glutathione synthesis in hepatocytes), and cytotoxic effects (inhibitor of cytochrome P450) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe its presence was confirmed for the first time in two German lakes: Langer See and Melangsee (Fastner et al 2003). Subsequently this toxin has been found in several other water bodies in Spain, the Czech Republic and France (Quesada et al 2006, Bláhová et al 2008, Brient et al 2009). In Poland, CYN was detected for the first time in samples from lakes of Wielkopolska -Bnińskie, Bytyńskie and Lubosińskie (Kokociński et al 2009).…”
Section: Presence Of Cyn In the Environmentmentioning
confidence: 69%